Common variants in Alzheimer’s disease and risk stratification by polygenic risk scores - Rojas, Itziar de; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Kerkmeijer-Jansen, Iris E.; Pedersen, Nancy L.; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nature Communications, 2021)
Genetic discoveries of Alzheimer’s disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer’s disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer’s disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer’s disease.